Hubungan karakteristik Ibu dan Perilaku Hidup Bersih Sehat (PHBS)Tatanan Rumah Tangga dengan kejadian Stunting - Asni Aprizah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Stunting is a short body condition based on the Height by Age index (height / age) which is an indicator of past nutritional status. The health status of individuals and families is closely related to their behavior. Clean and Healthy Living Behavior (PHBS) is essentially an individual or family preventive behavior from various diseases or health problems. Lubuk Rumbai Village is one of the areas where the PHBS RT coverage rate is very low (18.0%). The purpose of this study was to analyze the relationship between maternal characteristics and hygiene and healthy living habits in the household with the incidence of stunting in elementary school children in Tuah Negeri District, Musi Rawas Regency. The research method used was analytic observational and cross sectional design with Chi Square relationship test. The population in this study were students of SDN Lubuk Rumbai and SDN Simpang Semambang with a sample of 174 people. Collecting data using forms, questionnaires and measuring the child's height were assessed using the z score indec. The results of this study found that most of the stunting children (17 children) came from families with low-educated mothers and 15 children (15.2%) with working mothers and only 1 family applied household PHBS out of the 27 stunting children. While the statistical test resulted that there was no significant relationship between maternal education and the incidence of stunting with p value <0.05 (0.664) and there was no relationship between maternal employment status and the incidence of stunting with p value <0.05 (1,000), while between PHBS in the household With the incidence of stunting in elementary school children in Tuah Negeri District, there is a significant relationship with a p value <0.05 (0.004). It is hoped that the implementation of PHBS in households is a preventive effort because even though mothers are secondary targets, awareness of family members as the primary target Households with PHBS so they can avoid health problems including stunting.